Makna-makna gramatikal konstruksi verba denominatif dalam bahasa Indonesia - Nugraha, Danang Satria (citeus, 2021)
New words are constantly constructed as language evolves. Through morphological afixation, new words in Indonesian (bI) such as berfirman, menggembalakan, and direncanakan are classified as denominal verbs (VDn). VDn construction is the focus of this study. It aimed to describe the grammatical meanings of VDn construction in bI. Data of the study include the VDn constructions in bI. The data sources were (a) written bI in various texts and (b) the two online corpora containing bI data, www.sealang.net and www.corpora.uni-leipzig.de. Data were collected using observation and semi-corpus methods. During the analysis, referential match technique was used to identify the grammatical meanings of each VDn construction. Results are presented in a form of rules, tables, and descriptions. The study found that there are three main categories of grammatical meanings of VDn construction in bI, namely ‘action’, ‘process’, and ‘state’. First, the ‘action’ VDn includes ‘instrumental’, ‘benefactive’, ‘reciprocal’, and ‘repetitive.’ Second, the ‘process’ VDn consists of ‘locative’, ‘resultive’, and ‘reflective.’ Third, the ‘state’ VDn consists of ‘stative’ and ‘substantive.’ Further studies may pay attention on other construction of derived verbs, such as deadjectival verbs that can be analyzed and described using Semantic theories Kata-kata baru dibentuk seturut dengan perkembangan bahasa. Dengan afiksasi, kata-kata baru seperti berfirman, menggembalakan, dan direncanakan, yang terhimpun dalam klasifikasi verba denominatif (VDn) pada bahasa Indonesia (bI) diciptakan untuk merepresentasikan berbagai makna gramatikal. Fenomena konstruksi VDn tersebut merupakan objek kajian ini. Secara khusus, kajian ini disusun untuk mengidentifikasi dan mendeskripsikan makna-makna gramatikal konstruksi VDn dalam bI. Data kajian berwujud konstruksi VDn dalam bI. Sumber data berupa (a) wacana tulisan berbahasa Indonesia, dan (b) laman penyedia rekaman penggunaan bI dengan identitas www.sealang.net dan www.corpora.uni-leipzig.de. Data dikumpulkan menggunakan metode simak/observasi dan metode semi-korpus. Untuk tahap analisis, teknik padan referensial digunakan. Hasil analisis disajikan dalam bentuk kaidah, tabel, dan uraian deskripsi. Berdasarkan analisis, dapat dinyatakan bahwa sekurang-kurangnya terdapat tiga kategori utama makna gramatikal konstruksi VDn, yaitu ‘aksi’, ‘proses’, dan ‘keadaan’. Pertama, makna ‘aksi’ konstruksi VDn meliputi ‘instrumental’, ‘benefaktif’, ‘resiprokal’, dan ‘repetitif’. Kedua, makna ‘proses’ konstruksi VDn meliputi ‘lokatif’, ‘resultatif’, dan ‘reflektif.’ Ketiga, makna ‘keadaan’ konstruksi VDn meliputi ‘statif’ dan ‘substantif.’ Untuk kajian selanjutnya, konstruksi verba turunan yang lainnya seperti verba deajektival dapat dianalisis dan dideskripsikan berdasarkan ancangan teoretis Semantik.